Ocorrência e caracterização molecular de Cryptosporidium em cordeiros - Féres, F. C. [UNESP] (2009)
The occurrence of Cryptosporidium in fecal samples of lambs was determined in order to test correlations among the type of animal raising, feces consistence, index of oocysts elimination, animal age, and molecular characterization of species and genotypes involved in this parasitism. A total of 460 fecal samples were collected from lambs during the first 30 days of life, in various screeds of 21 farms. All samples were analyzed using malachite green negative coloration stain under microscopy. For molecular characterization of Cryptosporidium, on positive samples under microscopy, a nested PCR protocol was used for amplification of fragmentts from 18S rRNA gene or actin gene. It was found 6.7% of animals expeling oocysts of Cryptosporidium in feces of eight farms, without statistics relation among the analyzed indexes. The species and genotype involved were C. parvum type A 18S rRNA, C. parvum type B 18S rRNA and cervid genotype, which present a zoonotic potential of disease.